Application of the Sips model to the calculation of maximum adsorption capacity and immersion enthalpy of phenol aqueous solutions on activated carbons - Carvajal-Bernal, Ana Maria; Gomez-Granados, Fernando; Giraldo, Liliana; Moreno-Pirajan, Juan Carlos (European Journal of Chemistry, 2017)
The Sips model for heterogeneous systems was used to describe the immersion enthalpy, maximum adsorption capacity at three temperatures, namely, 283, 291 and 308 K; and interactions between phenol aqueous solutions and activated carbon modified on its surfaces by impregnation with 6.0 M HNO3 and 3.0 M H3PO4 solutions. Activated carbon properties, such as porosity, Brunauer-Emmett-Teller (BET) surface area and volume and size pore distributions, were determined using N2 adsorption at 77 K. Surface area values were calculated to be between 469 and 864 m2/g. Also, the pH at the point of zero charge, acidity and total basicity for the activated carbons were obtained. The result showed that the Sips model in addition to describe the phenol concentration in equilibrium can be used to study immersion enthalpy when 1/ns is equal to 1.